Characterising extrusive and intrusive magmatism at the Kipper Field, Gippsland Basin, using 3D seismic data. Issue 1 (1st December 2016) - Meeuws, Fun; Reynolds, Peter; Holford, Simon; Foden, John; Schofield, Nick
Abstract : Increased hydrocarbon exploration along rifted continental margins indicates the need of a better understanding of the impact and influence of igneous rocks on hydrocarbon systems as they are often present in these tectonic settings. The southern Australian margin contains several petroliferous sedimentary basins which contain Cretaceous-Cenozoic igneous rocks and is therefore an ideal study area to investigate both the positive and negative effects on hydrocarbon systems. In particular, the Kipper Field in the offshore Gippsland Basin forms an excellent example of a volcanic play, as it holds a 328 m gas column and 14 m oil leg sealed by a >100 m thick basaltic lava flow juxtaposed against a sealing fault. The basin also contains a number of cross-cutting and layer-parallel type intrusions, although their impact on the petroleum system is as-yet unclear. Seismic interpretation techniques such as spectral decomposition and opacity rendering combined with electrical log signatures allowed us to identify the lava flow and intrusions down dip from the fault. Whether this fault has acted as a conduit for the magma responsible for the lava flow is still unclear. Future work will aim to further delineate and constrain flow paths of the intrusive and extrusive rocks near the Kipper Field and their influence on the Kipper play. This study highlights the importance of volcanic rocks in hydrocarbon basins and the possible effect they can have on hydrocarbon systems.